Electrophysiological and morphological properties of interneurones in the rat dorsal lateral geniculate nucleus in vitro. - Williams, S R (1996)
1. Intracellular recordings were made from putative interneurones (n = 24) and thalamocortical (TC) projection neurones (n = 45) in slice preparations of the rat dorsal lateral geniculate nucleus (dLGN) in order to compare the electrophysiological properties of these neuronal types. 2. Intracellular injection of biocytin to electrophysiologically identified neurones (n = 34) revealed the morphology of putative interneurones (n = 4) to be similar to class B and that of TC neurones (n = 30) to be similar to class A Golgi-impregnated neurones. 3. Interneurones had resting membrane potentials (-52 mV) relatively positive to those of TC neurones (-63 mV), shorter time constants (36.8 and 58.2 ms, respectively), but similar steady-state input resistances (164 and 180 M omega, respectively). Steady-state voltage-current relationships were nearly linear in interneurones, but highly non-linear in TC neurones. 4. The structure of action potential firing evoked at the break of hyperpolarizing voltage transients was dependent upon neuronal type. Interneurones fired a single action potential or a burst of action potentials with a maximum frequency of < 130 Hz, whilst TC neurones fired a high frequency burst with a minimum frequency of > 250 Hz. In addition, well-defined burst firing of action potentials in response to depolarizing voltage excursions, from membrane potentials negative to -65 mV, could be evoked in TC neurones, but not in interneurones. 5. The directly evoked action potentials of interneurones were characterized by an initial slow pre-potential preceding the fast upstroke of the action potential. The amplitude and width of interneurones' action potentials were smaller than those of TC neurones and the amplitude and duration of the single action potential after-hyperpolarization were greater in interneurones. Both interneurones and TC neurones fired action potentials repetitively in response to suprathreshold voltage excursions, with interneurones demonstrating a greater degree of spike-frequency adaptation. Following a train of action potentials, interneurones and TC neurones generated a slow after-hyperpolarizing potential: in interneurones but not TC neurones this potential was followed by a slow depolarizing potential. 6. An intrinsic, subthreshold membrane potential oscillatory activity with a mean frequency of approximately 8 Hz was observed in interneurones. 7. Electrical stimulation of the optic tract evoked in interneurones apparently pure EPSPs, pure IPSPs or a mixture of EPSPs and IPSPs. EPSPs were found to be biphasic and mediated by the activation of non-N-methyl-D-aspartate (NMDA) and NMDA excitatory amino acid receptors. IPSPs and the response to the iontophoretic application of GABA were found to reverse between -65 and -70 mV. The application of GABAB receptor agonists failed to affect the membrane properties of six of seven interneurones tested. In addition spontaneous EPSPs and IPSPs were recorded in interneurones. 8. These results demonstrate that the electrophysiological properties of putative interneurones are distinct from those of TC neurones of the rat dLGN. The implications of these findings for the control of visual responsiveness of TC neurones are discussed.